Excellent long-range charge-carrier mobility in 2D perovskites - Kober-Czerny, M; Motti, SG; Holzhey, P; Wenger, B; Lim, J; Herz, LM; Snaith, HJ (Wiley, 2022)
The use of layered, 2D perovskites can improve the stability of metal halide perovskite thin films and devices. However, the charge carrier transport properties in layered perovskites are still not fully understood. Here, the sum of the electron and hole mobilities (Σμ) in thin films of the 2D perovskite PEA2PbI4, through transient electronically contacted nanosecond-to-millisecond photoconductivity measurements, which are sensitive to long-time, long-range (micrometer length scale) transport processes is investigated. After careful analysis, accounting for both early-time recombination and the evolution of the exciton-to-free-carrier population, a long-range mobility of 8.0 +/− 0.6 cm2 (V s)–1, which is ten times greater than the long-range mobility of a comparable 3D material FA0.9Cs0.1PbI3 is determined. These values are compared to ultra-fast transient time-resolved THz photoconductivity measurements, which are sensitive to early-time, shorter-range (tens of nm length scale) mobilities. Mobilities of 8 and 45 cm2 (V s)–1 in the case of the PEA2PbI4 and FA0.9Cs0.1PbI3, respectively, are obtained. This previously unreported concurrence between the long-range and short-range mobility in a 2D material indicates that the polycrystalline thin films already have single-crystal-like qualities. Hence, their fundamental charge carrier transport properties should aid device performance.